Germany's market transparency unit for fuels: Fostering collusion or competition? - Marco Horvath (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
To increase competition in the retail market for gasoline, Germany's Federal Cartel Office established the so-called Market Transparency Unit for Fuels (MTU). Drawing on a panel data set covering 6,834 stations in Germany and employing both fixed effect methods and a difference-in-difference approach, this study investigates the impact of the MTU on the price margins of gas stations. We find that the MTU fostered a more intense competition, with a reduction in price margins of 1-2 cents per liter. – – Mit dem Ziel den Wettbewerb auf dem Benzinmarkt zu erhöhen, wurde die so genannte Markttransparenzstelle für Kraftstoffe durch das Bundeskartellamt eingerichtet. Diese Studie untersucht daher, auf Basis eines Paneldatensatzes von 6.834 Stationen in Deutschland und unter Verwendung von sowohl Fixed-Effects-Methoden als auch eines Difference-in-Difference-Ansatzes, die Auswirkungen der Markttransparenzstelle auf die Preismargen von Tankstellen. Wir stellen fest, dass die Markttransparenzstelle für Kraftstoffe einen verschärften Wettbewerb auf dem Benzinmarkt, mit einer Reduzierung der Preismargen um 1-2 Cent pro Liter, gefördert hat.
Keywords: Q41; D43; D83; L13; 330; retail gasoline; market transparency; price margin; competition